Akibat Hukum Kuasa Lisan Pembuatan Akta Notaris - MAYSARAH DINDA ARISA BR. PULUNGAN (Recital Review, 2021)
Abstract Article 1793 of the Civil Code states that the authority can be given or received with a general deed, on underhanded deed, or even with a letter or orally. However, not all legal acts can be given to someone else orally. In the Supreme Court’s Ruling No. 08/Pdt G 2016 PN. Spt, Authenic Deed No 20 on October 28, 2008 on :…joining or discharging as a partner and the amendment of the Articles of Association of CV. Putra Jaya”made based on oral authorithy is suspected by the principal and revoked by the Sampu District Court The Objective of the research was to analyze the use of oral authority in the practice of making an authentic deed by Notary, his obligation to make an authentic deed which guarantee the rights of the persens appearing, and his Supreme Courts Ruling No 08 Pdt G 2016 PN.Spt. The research used juridical normative method and descriptive analytic approach which was aimed to get detailed and systematic description about the research problems .The data were gathered by conducting library research method, documentary study, and interviews and analyzed qualitatively.The result of the research showed that using oral authority in making an authentic deed was allowed as it is specified ini Article 1795 of the Civil Code. In Practice, Oral authentic in making an authentic deed was only  based on the Notary’s consideration and for the benefit of the principal. Prudential principle should be the responsibility of a Notary’s as it is specified in Article 16, paragraph (1), letter a, for being careful. A Notary has to anticipate the legal risk of making an authentic deed orally by being based on prudential principle according to UUJN (the Notarial Act) He has to be responsible for  has own negligence. For an authentic deed which is revoked or legally null and vold through the court’s verdict, a Notary can be imposed by a sanction by giving compensation materially and immaterally.   Keywords: Oral Authority, Notary, Authentic Deed